Drying, Roasting, and Calcining of Minerals - Battle, Thomas; Downey, Jerome; May, Lawrence; Davis, Boyd; Neelameggham, Neale; Sanchez-Segado, Sergio; Pistorius, Chris (The Minerals, Metals & Materials Series,, 2016)
The papers in this volume give the reader focused information on the important extractive metallurgy unit operations of drying, roasting, and calcining.